GEOCHEMISTRY OF THIRTEEN VORONIN TROUGH CORES, KARA SEA, EUROPEAN ARCTIC: HG AND AS CONTAMINANTS AT A 1965 TIMELINE - Siegel F.R.; Galasso J.J.; Kravitz J.H. (My University, 2001)
The potentially toxic elements Hg and As are found at high concentrations in surface/near-surface sediments from Arctic ocean cores collected from the Voronin Trough, Kara Sea, during 1965. The levels reach 2045 ppb for Hg and 270 ppm for As. Manganese high values (up to 1.27%) are also found in the cores’ surface/near-surface sections. Other heavy metals tracked by the Arctic Monitoring and Assessment Program (e.g., Cu, Ni, Pb, Sb, Ti, Zn) have baseline concentrations in the cores. The cores average >57% clay-size and >35% silt-size in their textural composition. The elevated contents may result from anthropogenic input for Hg and As with diagenesis adding to the As concentration. Possible sources for these elements are emissions and effluents from industry such as mining and smelting operations, and burning of fossil fuels in Siberia and the Urals. When discharged into the Kara Sea from Siberian catchments, the As and Hg likely attach to charged particulate surfaces of Fe oxy/hydroxides (for As) and particulate organic matter or clay minerals (for Hg). These are transported, entrained in ocean currents or adhered to pack ice, to the Voronin Trough where they deposit according to size and specific gravity.